DEVELOPMENT of (LKPD) DISCOVERY LEARNING-BASED FOR CLASS X SCIENCE STUDENTS OF ENVIRONMENTAL POLLUTION MATERIAL - Rohani Rohani; Siti Fatimah (Jurnal Penelitian Pendidikan IPA, 2022)
This research is based on Discovery Learning on environmental pollution material and aims to produce Student Worksheets to determine the feasibility test. This feasibility was tested by media experts and material experts, as well as by teachers and students. This type of research is based on the research and development (R&D) improvement of the ADDIE research model. The research sample amounted to 36 students. The instruments used are media and material validation questionnaires, student response questionnaires and teacher response questionnaires, and the feasibility of discover learning-based Student Worksheets based on pretest and posttest. The data analysis technique of this research is quantitative and qualitative. The validation results found that the development of this Student Worksheet was at the stage of the feasibility of the Student Worksheet material with an average of 82.00% of the most appropriate definition criteria and media experts assessed an average of 88.00% of the average percentage of the most probable criteria. Discovery learning based on the teacher's response to environmental pollution, the importance of the Student Worksheet is 82.75% with very interesting conditions. The level of validity assessed by the teacher on this Student Worksheet is obtained by a percentage of 90.00% which is stated to be very practical. And lastly, the results of the pretest and posttest showed that it was 0.74 where this number indicates that the two tests are stated to be very practical. With the average achievement of the pretest getting an average value of 8.92 while the average posttest score getting an increase of 9.72, therefore with the test questions it was found that students experienced an increase in knowledge after using the Participant Worksheet. Discovery Learning-based students on environmental pollution material